STRATEGI PENGEMBANGAN USAHA PETERNAKAN SAPI POTONG DI KECAMATAN TINANGKUNG UTARA KABUPATEN BANGGAI KEPULAUAN - Jibran Malotes (Universitas Tadulako, 2016)
This is a descriptive qualitative research aimed at determining the development strategy of cattle farming system in North Tinangkung sub district of Banggai Kepulauan district. The research location was purposively determined where 45 respondents samples were selected using a random sampling technique. Data obtained was analyzed using SWOT analysis. Based on the SWOT analysis, the main strategy recommended for developing the cattle farming system is S-O (Strengths-Opportunities) strategy with strategy formula including (1) optimizing and developing internal capability of cattle farmers and utilizing the available resources in order to improve the scale of the cattle farming system leading to more advanced system, (3) cooperating with local government to create a more effective marketing networking in order to meet demand which is not yet achieved, and (3) establishing business partnership with government and third party by utilizing the kinship and mutual cooperating interaction of the rural community. Programs implemented will be (1) enhancing the quality of human resources, (2) developing distribution networking and marketing information system, and (3) developing land and cattle feed technology. Keywords: Cattle farming system, Strategy, and SWOT.